Rancang Bangun Mesin Pembuatan Filament 3D Printing Dari Kemasan Mineral - Zulkarnein, Faruq Akbar; Pristiansyah, Pristiansyah; Rollastin, Boy (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Plastic plays an important role in everyday life, especially as food and beverage packaging. However, uncontrolled use of plastic causes environmental problems, with plastic waste in Indonesia reaching 64 million tons per year. This study aims to utilize plastic bottle waste as a material for making 3D filaments, which can reduce the amount of plastic waste and support recycling. Data collection involves identifying problems, determining machine components following the stages in the VDI 2222 method. From the results of the experiment in determining the optimal size of cutting plastic bottles, namely a width of 9 mm and a thickness of 0.37 mm. Before making filaments, plastic bottles must be cleaned and heated to remove motifs that can affect the quality of the filament.